From Patchwork to Framework: Expert Interview Insights on Establishing a Bioethics Council for Canada - Lapteva, Alice; Bubela, Tania; Chandler, Jennifer; Knoppers, Bartha; Upshur, Ross; Ravitsky, Vardit; Illes, Judy (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Canada has historically relied on a system of ad hoc committees for ethical guidance on public health and science policy, unlike the more centralized approach of more than 140 countries worldwide. Here, drawing on interviews with leaders across the country, we offer a perspective on the imperative and a strategy for a coordinated, Bioethics Council for Canada structured to ensure proactive thinking, provide rapid responses, and engage the public on urgent bioethics matters concerning the health and well-being of Canadians.